Proprioception and flexibility profiles of elite synchronized swimmers - Cho, N. M. Y.; Giorgi, H. P.; Liu, K. P. Y.; Bae, Y.-H.; Chung, L. M. Y.; Kaewkaen, K.; Fong, S. S. M. (Perceptual and Motor Skills, 2017)
This study compared the full-body flexibility and joint proprioception (on land and underwater) of (a) 20 elite female synchronized swimmers (mean age±standard deviation=18.5±1.9 years) and (b) 20 college female swim team members with no training in synchronized swimming (control participants; mean age±standard deviation=20.6±1.3 years). Flexibility of the trunk and upper and lower limbs was measured using plastic tape and a goniometer, respectively. Joint proprioception (joint position sense) of the upper and lower limbs on land and underwater was measured by an active joint angle repositioning test. Principle outcome measures were passive joint range of motion (flexibility) and active joint repositioning error (proprioception). Multivariate analysis of covariance revealed that, compared with control swimmers, synchronized swimmers had greater passive joint ranges of motion in the spinal and upper and lower limb joints (p<.05) and fewer active joint repositioning errors in the shoulder, wrist, and ankle on land (p<.05) and in the hip and ankle underwater (p<.05). These results help characterize peak synchronized swimmer capabilities, provide valuable reference details for coaches, and may be useful for talent identification and skill development in this sport.